The deeds of the Neapolitan Bishops
1 online resource.
Keywords: "In the early Middle Ages Naples underwent huge changes. She was able to acquire complete independence from the Byzantine Empire and to emerge as one of the major powers in Southern Italy. Moreover, Naples avoided to become part of the Frankish Empire, to be subdued by the Lombards of Southern Italy and to be attacked by the Muslims, who had conquered Sicily. which is the only medieval historical text composed in Naples before the 14th century. The Deeds of the Neapolitan Bishops not only reports the biographies of the Neapolitan bishops during those centuries, but also describes the history of Naples and the relationships the Neapolitans had with their dangerous neighbors. This volume presents the analysis, Latin text, English translation, and historical commentary of this work, thus offering an important contribution for a better understanding of early medieval southern Italian (and Mediterranean) history. The book will appeal to scholars and students of chronicles, Naples, and Church history in early medieval Italy, as well as all those interested in medieval Europe and the Mediterranean"--